2021
DOI: 10.1108/ijge-12-2020-0201
|View full text |Cite
|
Sign up to set email alerts
|

Gender role (in-)congruity and resource-provider gender biases: a conceptual model

Abstract: PurposeExisting entrepreneurship literature has provided mixed evidence as to whether resource providers discriminate against female-led innovative start-up ventures in their resource commitment decisions either in terms of the likelihood or conditions of resource provision. While some studies revealed evidence indicative of negative discrimination against female entrepreneurs, others have provided evidence suggestive of positive discrimination. In light of these divergent findings, the purpose of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Are lower-level women employees perhaps expecting more gender-based solidarity from the very few women top managers than the latter are either capable of or willing to provide (e.g., to avoid gender-based favoritism), therefore perceiving them as cold “queen bees” (e.g., Mavin, 2006) and reducing, subsequently, their commitment to supporting their women bosses’ innovation strategies? Is this relation reversed in entrepreneurial firms where the power distance between top managers and employees is rather small (e.g., Dai et al, 2019) and/or organizations where women top managers are perceived as warm and employee-oriented rather than instrumental and self-oriented by lower-level women employees (cf., Eagly & Karau, 2002; Tonoyan & Strohmeyer, 2021)? We invite scholars to explore various contingencies likely to bound the cross-level interaction between top managers and employees , and if and how such “leader-member exchange” (Dulebohn et al, 2012) is consequential for firm innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are lower-level women employees perhaps expecting more gender-based solidarity from the very few women top managers than the latter are either capable of or willing to provide (e.g., to avoid gender-based favoritism), therefore perceiving them as cold “queen bees” (e.g., Mavin, 2006) and reducing, subsequently, their commitment to supporting their women bosses’ innovation strategies? Is this relation reversed in entrepreneurial firms where the power distance between top managers and employees is rather small (e.g., Dai et al, 2019) and/or organizations where women top managers are perceived as warm and employee-oriented rather than instrumental and self-oriented by lower-level women employees (cf., Eagly & Karau, 2002; Tonoyan & Strohmeyer, 2021)? We invite scholars to explore various contingencies likely to bound the cross-level interaction between top managers and employees , and if and how such “leader-member exchange” (Dulebohn et al, 2012) is consequential for firm innovation.…”
Section: Discussionmentioning
confidence: 99%
“…In industry sectors where gender diversity is normatively accepted, investors are more likely to perceive it as beneficial to the firm performance. Such perceptions are also likely to become reinforced by their “second-order gender beliefs” (cf., Bordalo et al, 2019; see also, Tonoyan & Strohmeyer, 2021, p. 234; Jennings & Tonoyan, 2022), that is, beliefs about other stakeholders’ gender beliefs. In contrast, in industries where gender diversity has not yet gained normative acceptance, investors may see it as irrelevant or even detrimental to the firm performance (Zhang, 2020).…”
Section: Contingenciesmentioning
confidence: 99%
“…The study also found that female CEOs who lead businesses tend to engage in new and innovative business practices (Prabowo and Setiawan, 2021). Because females are less likely to reach the role of CEOs in major corporations, gender inequalities are likely to emerge as a result of resource suppliers’ judgments of business female-leading male startup firms as less capable than equally qualified male startups (Tonoyan and Strohmeyer, 2021). Interestingly, the results from the entrepreneurship area correspond with earlier findings regarding females assuming a stereotypically male position of an entrepreneur, and also, the findings from more recent research indicating that women are penalized for their achievement when ascending to leadership positions (Toneva et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jacobs et al (2010) reported that women working in roles incongruent with their Effects of gender roles perceived gender roles had higher levels of work stress than women working in roles that are perceived congruent with their gender roles, and as a result, the level of negative work outcomes was higher. At the same time, perceived role mismatch results in lower performance expectations in male-dominated jobs with the stereotypical perceived characteristics of women (Tonoyan and Strohmeyer, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%